2022
DOI: 10.24136/oc.2022.018
|View full text |Cite
|
Sign up to set email alerts
|

A review of inflation from 1906 to 2022: a comprehensive analysis of inflation studies from a global perspective

Abstract: Research background: Inflation has always been the core issue of economic research and there are many academic research achievements in this field. In recent years, global inflation has intensified, and many scholars focus on research in this field again, providing certain reference value for countries around the world to formulate corresponding macro policies. Purpose of the article: The five-year impact factors are used as the evaluation criteria in this paper, and 1,637 high-quality documents on inflation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Bibliometrics is one of the most critical research domains that quantitatively analyzes patterns in scientific literature to understand global trends and the intellectual structure of the field analyzed (Cobo et al, 2011;Mishra et al, 2020). While analyzing secondary data from digital scientific databases, it facilitates a methodical, transparent, and replicable review process, consequently bolstering the reliability and overall quality of the review (Velasco-Muñoz et al, 2022;Wang et al, 2022a).…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometrics is one of the most critical research domains that quantitatively analyzes patterns in scientific literature to understand global trends and the intellectual structure of the field analyzed (Cobo et al, 2011;Mishra et al, 2020). While analyzing secondary data from digital scientific databases, it facilitates a methodical, transparent, and replicable review process, consequently bolstering the reliability and overall quality of the review (Velasco-Muñoz et al, 2022;Wang et al, 2022a).…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al researched the carbon-neutral energy consumption and emission volatility: the causality analysis of ASEAN region. They found that the green consumptions decrease the CO2 emissions in Asean countries [28][29][30][31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on this paradigm, the new Keynesian school had achieved a good fit for real-world data, and they believed that both supply shocks and demand shocks played pivotal roles in economic cyclical fluctuations. Furthermore, 941 they contended that both fiscal and monetary policies exerted substantial influence on these economic cyclic variations (Wang et al, 2022).…”
Section: The Cause Of Bcsmentioning
confidence: 99%